Scaffolding in Mobile Science Enquiry-based Learning Using Ontologies - Sohaib Ahmed; David Parsons; Mandia Mentis (European Alliance for Innovation (EAI), 2012)
The use of ontologies has become increasingly widespread in many areas, particularly in technology enhanced learning. They appear promising in supporting knowledge representation and learning content creation for domains of interest. In this paper, we show how ontology-based scaffolding has helped mobile learners to perform scientific enquiry investigations. Enquiry-based learning aims to provide educational activities and tools to assists students to learn science by doing science. In this study, a design science research approach was taken to creating an ontology-driven application for a science content domain, which has been evaluated with high school science students. The results showed the significant value of ontologies in scaffolding learning content in such enquiry-based learning environments. With this application, students were found to learn science in more meaningful and engaged ways as well as developing positive attitudes towards mobile learning.